The work of the Spirit: pneumatology and Pentecostalism - Welker, Michael (William B. Eerdmans Pub. Co., 2006)
Ever since the sensational Azusa Street Revival in 1906, the global Pentecostal church has continued to explode numerically, pushing theological debates on the Holy Spirit to the forefront. This insightful collection draws together theologians, scientists, and Pentecostal scholars to make connections between the study and experience of the Holy Spirit. The authors begin by addressing theological implications before moving on to the Pentecostal experience, finally connecting the Spirit to scientific and philosophical reflections.